EPIDEMIOLOGICAL AND CLINICAL PROFILE OF HUMAN POISONING IN CAMPINA GRANDE, PARAÍBA - Luana Gonçalves de Souza; Ana Letícia Alves de Carvalho; Rodrigo Pinheiro Fernandes de Queiroga; Sayonara Maria Lia Fook; Saulo Rios Mariz (Artefactum - revista de estudos interdisciplinares, 2026)
Epidemiological and clinical analysis of poisonings, notified by CIATox-CG, from 2017 to 2023.The data were collected from the Brazilian Intoxication Data System (DATATOX) and analyzed using descriptive statistics. The research project was approved by the CEP HUAC. Among the victims of poisoning or intoxication, female patients predominated, young and young adults (aged 20 to 59 years), students, and those with incomplete primary education. The most prevalent causal agents were venomous animals and medications, with the most common circumstances being accidental and suicide attempts. Among venomous animals, scorpions stood out, and among medications, benzodiazepines were most prevalent. The year with the highest percentage of cases was 2023, however, the largest increase was from 2019 to 2020. The occurrences are more common in urban areas and in the municipality of Campina Grande. Most cases were mild, with the main outcome being recovery without sequelae and the main clinical manifestation being dermatological pain. These findings may be useful for the prevention and control of poisoning and venomous animal accidents in Campina Grande (PB) and the surrounding region.